CPLD-based system for the quadrature digital upconverter - Vdovychenko, Yegor I. (Видавництво Львівської політехніки, 2010)
In this paper CPLD-based realization of a radio technical system meant for the quadrature digital up converter control being used in the communication systems of special purpose.
Keywords: AHDL; VHDL; CPLD; IP-CORE; ALTERA; AD9856